POLA PERGERAKAN WISATAWAN NUSANTARA iGENERATION BERWISATA DI BALI PADA MASA PANDEMI COVID-19 - Azra, Akhmad Farrkhan Farrabi; Dewi, NGAS.; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2023)
This writing analyzes how the movement patterns of iGeneration Nusantara who visited Bali during the COVID-19 pandemic. The purpose of writing is to determine the characteristics of iGeneration domestic tourists, and to analyze the movement patterns of iGeneration domestic tourists. In this paper the researchers collected data through questionnaires, and literature review. The type of data used is in the form of qualitative descriptive data by 100 respondents who are generated based on a questionnaire with the criteria set are iGeneration domestic tourists who travel in Bali with a maximum age of 27 years. The patterns produced by iGeneration domestic tourists based on 100 respondents, will get the patterns and characteristics. This tourists are dominated by male visitors as much as 65% and women 35%. The trip carried out with friends/partners and family in this writing the dominant iGeneration domestic tourists generally use car and plane transportation when going to Bali. Length of stay for 3-4 days using hotel accommodations, villas, homes of relatives and getting through social media and verbal information. The pattern obtained is dominated by 77% Complex Neighborhood pattern, 11% Destination Region Loop 7%, Chaining Loop, and 5% Stop Over pattern. This finding is expected for industry players and developers to further promote other tourist attractions so that they can be evenly distributed. For the government in the future, public transportation routes can be made to connect tourist attractions, so that it can make it easier for tourists who use public transportation.